PENGARUH PENGUNGKAPAN OTHER COMPREHENSIVE INCOME TERHADAP ASIMTERI INFORMASI YANG DIMODERASI OLEH KUALITAS AUDIT PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BEI TAHUN 2012-2016 - Nini Sumarni (JURNAL AL-IQTISHAD, 2019)
ABSTRACTThe changes in accounting standards in Indonesia that use international-based standards are the focus of important attention for company management, because company management has to report other comprehensive income. Other comprehensive income components contain high assumptions, estimations, and judgments from the management, therefore high audit quality is being able to support a decrease in information asymmetry. This study aims to analyze the effect of disclosure of other comprehensive income on information asymmetry in financial sector companies listed on the Indonesia Stock Exchange in 2012-2016. This type of research is descriptive verification. The dependent variable in this study is information asymmetry. The independent variable in this study uses the OCI ratio, while the audit quality as a moderator variable uses a dummy variable, where the big four KAP is given value of 1 and the non-big four KAP is given a value of 0. The control variable is the size of the company measured by natural asset logarithms. This study uses secondary data, namely financial data sourced from the website. The results of the study through the F test is a significant value of 0.003 (<0.005).  Keywords: other comprehensive income, information asymmetry, audit quality, company size.